BECOMING PLATFORM: DISRUPTION, MASCULINITY, AND INFRASTRUCTURE - Bozzi, Nicola (AoIR Selected Papers of Internet Research, 2026)
My contribution is a theoretical conceptualization of the platform as a disruptive figure - not only in the infrastructural turn towards what scholars have defined as the “platformisation” (Poell, Nieborg & Van Dijk, 2019) of a diverse range of industries, but also as a political metaphor and a vector for social identification.My main focus is on the rise of powerful, hypermasculine figures like Donald Trump, Elon Musk, and Joe Rogan, who notably leverage the concept of (dis)trust towards “mainstream” and “legacy” media in favour of tech platforms like Musk’s own X (formerly known as Twitter) or alt-tech platforms like Donald Trump’s Truth Social or Rumble. While these platforms are presented with a stated emphasis on free speech as a universal value, their usage is also driven and/or associated with strong, even authoritarian personalities, usually characterized by a hyper-masculine persona and US-exceptionalist attitudes.My proposal is thus framing the “platform” and “platforming practices” as a key conceptual scaffolding for reading the current cultural momentum of these figures. Positioning the “becoming platform” of Rogan, Musk, or Trump (each of whom have come to embody platforms of sorts – respectively: JRE, X, Truth Social) in the context of the dangerous emergence of a “platformed personality capitalism” founded on “personality as infrastructure” (Rosamond, 2023), I discuss the identity politics of these powerful men and the way they function as discursive catalysts for platformisation as an urgent cultural and political issue.